Inclusion of children with airway disease for the development of spirometry reference data. Issue 4 (April 2016) - Lum, Sooky; Stocks, Janet
We wish to thank A. Hüls and colleagues for their interest in our recent paper [1], and the opportunity to clarify the rationale behind the conclusions we reached, which differ from their own. Despite the title of their letter, it is important to emphasise that we did not recommend inclusion of symptomatic children, those with a prior history of adverse exposures, or those with a current respiratory illness such as asthma, when establishing spirometric reference equations, where international standards regarding definition of health may need to be adhered to. Indeed we state clearly in the discussion that under such circumstances the target sample size may have to be increased by at least 30% to account for such exclusions, a proportion not dissimilar to that reported by Hüls et al . [2] What was demonstrated by our results is that when carrying out epidemiological studies such as the SLIC study (Size and Lung function In Children)[3], the primary aim of which was to ascertain the extent to which ethnic differences in lung function can be attributed to differences in physique and socioeconomic factors, inclusion criteria can be broader without biasing results. This not only renders the results more generalisable but has considerable practical and economic benefits. Excluding current/chronic lung disease, population samples for children's lung function can be relatively inclusive http://ow.ly/X0enM